Bathiymetric distribution of Pleuromamma (Copepoda, Calanoida) species in the Indian Ocean - Jayalakshmi, K V (Indian Journal of Fisheries, 2011)
Based on ihe analysis of 204 zooplankton samples from the stratified depths in the Indian oceancollected during the International Indian Ocean Expedition (IIOE), the distribution of the genusPleuromamma, a Calanoid Copepod, was studied. Seven species, viz. Pleuromamma indica, P. gracilisP. piseki, P. abdominalis, P. borealis, P. xipias and P. quadrungulala, in the order of their abundance,and 1 variety of the genus P. abdominalis abyssal is were observed. Vertical distribution of speciesof Pleuromamma showed that they were inversely correlated with depth. Among the Pleuromammaspecies, P. indica could survive in an environment of low dissolved oxygen and lower depths of watercolumn, whereas P. xipias and P. abdominalis could survive in an environment of high dissolved oxygenand at almost all depths of water column. Multiple regression analysis of the data suggested that lightintensity, further depth stratification, seasonal variations, water currents and the interaction effects oftemperature with dissolved oxygen and nutrients could provide a more pronounced prediction of thetotal abundance of the Pleuromamma species. Diversity function H (s), in relation to latitude wasa bell-stuped normal curve. HO) was linearly related to evenness index, e, and was a perfectly slopingup line. These relations were highly pronounced at lower depths of water column and in the highlyproductive regions.